2011
DOI: 10.4103/0974-9233.80694
|View full text |Cite
|
Sign up to set email alerts
|

A retrieval system for patients with avoidable blindness due to diabetic retinopathy who do not present for ophthalmic assessment in Oman

Abstract: Background:Many patients with diabetes do not present for eye examinations, foregoing the recommended management for diabetic eye care. Proactive steps are being taken in Oman to retrieve defaulters (patients who do not present or “no-show”) with Sight Threatening Diabetic Retinopathy (STDR). We present the outcomes of the defaulter retrieval system in five regions of Oman in 2009.Materials and Methods:Ophthalmologists examine eyes periodically, family physicians focus on primary prevention of Diabetic Retinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…The quality appraisals of the included studies (n = 53 24,[147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][163][164][165][166][167][168][169][170][172][173][174][175][177][178][179][180]182,184,185,187,[190][191][192]194,195,197,199,[201][202][203][204][205][206][207][208]…”
Section: Quality Of Included Studiesunclassified
See 2 more Smart Citations
“…The quality appraisals of the included studies (n = 53 24,[147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][163][164][165][166][167][168][169][170][172][173][174][175][177][178][179][180]182,184,185,187,[190][191][192]194,195,197,199,[201][202][203][204][205][206][207][208]…”
Section: Quality Of Included Studiesunclassified
“…On the basis of expressed importance, domains judged to be important in the included studies were 'environmental context and resources' (19 studies 148,152,154,155,158,160,161,166,170,179,[185][186][187]189,191,194,199,201,207 ), 'knowledge' (19 studies 152,[158][159][160][161]165,[167][168][169][173][174][175]181,190,191,193,195,200,205 ), 'memory, attention and decision processes' (11 studies 156,166,170,[179][180][181][182]187,189,193,…”
Section: Expressed Importancementioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] A variety of factors contributed to the high noncompliance rate, such as transport, absence of a decision maker, fear of laser treatment, socioeconomic barriers, health system barriers, educational barriers, and cultural barriers. [21][22][23] According to our clinical experience, the same issues occurred in Chinese patients with diabetes, but the underlying factors were unclear. Moreover, many patients defaulted from the laser treatment in progress, although many reports showed that the supplementary laser photocoagulation and the subsequent follow-up were as important as the initial laser sessions.…”
mentioning
confidence: 91%
“…Studies of DR services in Pakistan, Oman and China reported that 29.5%, 22.8% and 27.9% of patients respectively did not initiate treatment. [7][8][9] In the study in China, an additional 17.6 % did not complete the treatment course, for reasons including being unaware of the importance of treatment and the need to complete the full course, and fear of treatment. 9 In high-income countries the proportion of patients not completing treatment tends to be lower than in low-income countries but still significant.…”
Section: Introductionmentioning
confidence: 99%